Análisis pragmático de la jerga de los estudiantes de la Unidad Educativa Puruhá - Becerra Gavilanes, Emily Micaela (2025)
This research, entitled “Pragmatic analysis of the slang used by students at the Puruhá Educational Unit,” analyzes the use of youth language as a communicative and sociocultural manifestation in educational contexts. The main objective was to analyze the slang used by students from a pragmatic perspective, identifying its functions, contextual meanings, and the speech acts that shape its everyday use. The research was carried out using a qualitative, exploratory, and descriptive approach of a basic nature in a field context. The participants were second-year high school students at the Puruhá Educational Unit. The corpus was selected from transcripts of spontaneous dialogues collected in natural settings, such as the classroom and the recreation area. Data collection techniques included open-ended interviews and content analysis, supported by tools such as a script of generative questions and analysis tables. The findings show that students use various colloquial expressions, such as chuta, bacán, ñaño, valemos madres, among others, whose pragmatic functions are associated with expressive, directive, representative, vocative, and phatic speech acts. These linguistic expressions are fundamental because they represent the identity of each student, whether individual or group, and play important roles in identity formation, group bonding, emotional expression, cultural preservation, and verbal communication. Similarly, the different expressions suggest that they are linked to education and the ability to participate in other types of groups, taking values into account. In short, it is established that student slang should not be denigrated but rather accepted in society. An interpretive approach grounded in pragmatism supports countless languages in the educational context, promotes quality education, and encourages cultural understanding